Influence of the carbon atom numbers and the structure of collectors on the coal fines flotation. Issue 1 (1st January 2017) - Kang, Wenze; Hu, Jun
Abstract: This paper highlighted measuring the contact angle, the wetting heat and the IR spectrum before and after interactions between eight alkanes and coals to investigate the influence of the alkane structure and the number of carbon atoms on the coal surface hydrophobicity. The coal fines flotation tests were conducted with alkanes as collectors. The results show that after different alkanes acted on the coal samples, when the carbon numbers are same, both the contact angle and the wetting heat of isoparaffins were higher than those of the normal alkane. When the number of carbon atoms was 12, the contact angle and the wetting heat reached the maximum values after alkanes interacted with coals. The yield of the clean coal, the combustible material recovery and flotation perfect indicators of the isododecane were higher than those of the dodecane by 3.62, 4.08 and 0.96% respectively under the same condition of flotation. The ash content of the clean coal was also higher than that of the dodecane by 0.91%. This study shows that the collecting ability of the isoparaffin was superior to that of normal alkanes, while the flotation selectivity of the normal alkane was better than that of the isoparaffin.